WARLI PAINTING: AESTHETICS OF INDIGENOUS ART FORM OF INDIA - Rao, Mrutyunjaya (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This article delineates Warli paintings and its characteristics. Warli art was first discovered in early seventies. No record found about the exact origins of this tribe and its roots. It may belong to 10th century AD., when man learn to build the walls of the house. Warli art is a vivid expression of daily and social life of the tribe named as Warli of Maharashtra. Their art is entwined with their life and rustic magic, rituals, God and goddesses, harvest seasons, marriage scenes painted on the prepared walls of their homes, later they shifted to canvas, paper, cloth etc. as per the demand. Primarily this art form is painted by women only later men also joined. It’s a pure and unadulterated art form. Warli painting is simple and comprised of geometric forms and relegated the academic rules like proportions, perspective. Tarpa dance and Caukat are the most striking features of Warli art. In the early 70’s Artist Bhaskar Kulakarni came to Warli tribe and taught them, how to make their paintings more substantial and influenced many contemporary artists and achieved international fame.